Trees and shrubs suitable for the construction of agroforestry systems in a temperate climate and their use in economic activities: a study in Bulgaria - Ivan Bozhikin (Journal of Innovations and Sustainability, 2023)
Purpose. The study aims to (i) discover the various trees and shrubs appropriate for building agroforestry systems in Bulgaria’s temperate climate and their possible use in various economic activities, (ii) identify the contribution of Bulgarians’ agroforestry systems to the three dimensions of sustainable development.